2014
DOI: 10.1504/ijmp.2014.065229
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management and corporate governance: the Ghanaian experience

Abstract: Though a number of studies have been carried out in corporate governance and also on companies listed on the Ghana Stock Exchange, this paper is the first in the country that considers the relationship of Corporate Governance (CG) in relation to Earnings Management (EM). It increases the understanding of EM and its relationship with CG of listed firms. The study used the cash flow approach and the modified Jones model in estimating total accruals discretionary accruals (measure of earnings management). It also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This implies that as the board gets larger, inefficiencies in the oversight function is increased thereby causing an increase in earnings management and vice versa. This finding is supported by Agyekum, Aboagye‐Otchere, and Bedi (2014), who argue that board size presents a positive effect on earnings management. Thus, firms with larger boards are ineffective in their monitoring role and consequently tend to partake more in earnings management activities.…”
Section: Literature Reviewmentioning
confidence: 60%
See 2 more Smart Citations
“…This implies that as the board gets larger, inefficiencies in the oversight function is increased thereby causing an increase in earnings management and vice versa. This finding is supported by Agyekum, Aboagye‐Otchere, and Bedi (2014), who argue that board size presents a positive effect on earnings management. Thus, firms with larger boards are ineffective in their monitoring role and consequently tend to partake more in earnings management activities.…”
Section: Literature Reviewmentioning
confidence: 60%
“…Some studies have investigated the effect of corporate governance on earnings management. Agyekum, Aboagye‐Otchere, and Bedi (2014) found that the independence of directors presents negative implications on earnings management. Hence, independent directors help in minimizing the prevalence of earnings management practices among entities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation